Diskursus Metodologi Studi Hadis Kontemporer Analisa Komparatif antara Pendekatan Tradisional dan Pendekatan Revisionis - Ali Masrur (JOURNAL OF QUR'AN AND HADITH STUDIES, 2012)
Hadith studies in contemporary period developed into two different approaches: traditional and revisionist approach. Fuat Sezgin, Nabia Abbott, and M.M Azami were the students of Hadith using traditional approach. In studying Hadith, they departed from Islamic basic assumption and scientific method, especially the method of Hadith and rijal sciences. In their works, they never criticized Islamic sources. They believed in what was said, transmitted, interpreted, and written by early muslim generation as what really happened. On the contrary, Ignaz Goldziher, Joseph Schacht, and G.H.A. Juynboll were the students of Hadith using revisionist approach who always see Islamic sources critically and sceptically. They didn’t believe in the authenticity of the Islamic sources before they proved that the authenticity of the sources was verified by applying a source critical method. The use of a source critical method was to be special characteristic of revisionist approach in studying the prophetic Hadith.